Three-dimensional verification of 125I seed stability after permanent implantation in the parotid gland and periparotid region. Issue 1 (December 2015) - Fan, Yi; Huang, Ming-Wei; Zheng, Lei; Zhao, Yi-Jiao; Zhang, Jian-Guo
Abstract Objective To evaluate seed stability after permanent implantation in the parotid gland and periparotid region via a three-dimensional reconstruction of CT data. Material and methods Fifteen patients treated from June 2008 to June 2012 at Peking University School and Hospital of Stomatology for parotid gland tumors with postoperative adjunctive125 I interstitial brachytherapy were retrospectively reviewed in this study. Serial CT data were obtained during follow-up. Mimics and Geomagic Studio software were used for seed reconstruction and stability analysis, respectively. Results Seed loss and/or migration outside of the treated area were absent in all patients during follow-up (23–71 months). Total seed cluster volume was maximized on day 1 post-implantation due to edema and decreased significantly by an average of 13.5 % (SD = 9.80 %; 95 % CI, 6.82–17.68 %) during the first two months and an average of 4.5 % (SD = 3.60 %; 95 % CI, 2.29–6.29 %) during the next four months. Volume stabilized over the subsequent six months. Conclusions 125 I seed number and location were stable with a general volumetric shrinkage tendency in the parotid gland and periparotid region. Three-dimensional seed reconstruction of CT images is feasible for visualization and verification of implanted seeds in parotid brachytherapy.